The Role of The Subject Teacher Conference (MGMP) For The Progress of Subject Teacher - Ulfa, Syarifah Widya; Marhamah, Agita; Nasution, Nurhafizah; Rahayu, Putri; Aqamarina, Tadzkia Nasywa (research, training and philanthropy institution Natural Aceh, 2023)
This research aims to know the role of MGMP in the progress of subject teachers. The research method used was qualitative with a survey research design. The instrument used in data collection was questionnaires distributed online through Google Forms, with 105 respondents. The data analysis technique is an interactive model that goes through three stages: data reduction, data presentation and conclusion. Then proceed with triangulation. The results showed that MGMP has a high role in improving the quality of subject teachers because, in MGMP, there are many things discussed, such as improving teacher performance, teaching materials or materials, curriculum, about good PBM so that the material reaches students, lesson plans, how to deal with students and compile exam questions. This study concludes that MGMP is an essential forum for teachers to conduct deliberations to solve further everything that exists to improve the quality of the times. Through more frequent MGMP meetings, it can achieve educational goals and make teachers more professional. The study's implication is to advise the government that MGMP is very influential on the progress of subject teacher performance so that the government is more concerned about non-formal organizations and members in them.